The Effect of Three Methods of Aromatherapy, Massage and Aromatherapy–Massage on Muscular Pain Rate of Female Athletes in Isfahan (Iran) - Mansoureh Arefinia; Behnam Ghasemi; Sajad Arefinia; Mohammad Reza Moradi (Sport Sciences and Health Research)
As exercise influences body and mind, the physical and psychological factors influence sport and sport performance as well. The aim of this study was to evaluate the effect of three methods of aromatherapy, massage and aromatherapy–massage on muscle pain of physical fitness girls of Isfahan. 32 athletes who participated in the 1390 Fajr tournaments were selected by the available method and divided into equal groups of control, aromatherapy, massage and aromatherapy–massage. Demographic questionnaire and Talug muscle soreness questionnaire were used to collect data. For data analysis, dependent and independent t tests were used. The results showed that except for aromatherapy group, there was a significant difference in the rate of muscle pain before and after the intervention (P<0.05) between control and massage and between control and aromatherapy-massage groups. It can be concluded that aromatherapy, massage and aromatherapy–massage are effective interventions to reduce muscle pain in athletes in the competitions.